Colchicine prevents disease progression in viral myocarditis via modulating the NLRP3 inflammasome in the cardiosplenic axis. (17th February 2022) - Pappritz, Kathleen; Lin, Jie; El‐Shafeey, Muhammad; Fechner, Henry; Kühl, Uwe; Alogna, Alessio; Spillmann, Frank; Elsanhoury, Ahmed; Schulz, Rainer; Tschöpe, Carsten; Van Linthout, Sophie
Abstract: Aim: The acute phase of a coxsackievirus 3 (CVB3)‐induced myocarditis involves direct toxic cardiac effects and the systemic activation of the immune system, including the cardiosplenic axis. Consequently, the nucleotide‐binding oligomerization domain‐like receptor pyrin domain‐containing‐3 (NLRP3) inflammasome pathway is activated, which plays a role in disease pathogenesis and progression. The anti‐inflammatory drug colchicine exerts its effects, in part, via reducing NLRP3 activity, and has been shown to improve several cardiac diseases, including acute coronary syndrome and pericarditis. The aim of the present study was to evaluate the potential of colchicine to improve experimental CVB3‐induced myocarditis. Methods and results: C57BL6/j mice were intraperitoneally injected with 1 × 10 5 plaque forming units of CVB3. After 24 h, mice were treated with colchicine (5 μmol/kg body weight) or phosphate‐buffered saline (PBS) via oral gavage (p.o.). Seven days post infection, cardiac function was haemodynamically characterized via conductance catheter measurements. Blood, the left ventricle (LV) and spleen were harvested for subsequent analyses. In vitro experiments on LV‐derived fibroblasts (FB) and HL‐1 cells were performed to further evaluate the anti‐(fibro)inflammatory and anti‐apoptotic effects of colchicine via gene expression analysis, Sirius Red assay, and flow cytometry. CVB3 + colchicine mice displayed improved LV function compared with CVB3 + PBS mice, paralleled by a 4.7‐fold ( P < 0.01) and 1.7‐fold ( P < 0.001) reduction in LV CVB3 gene expression and cardiac troponin‐I levels in the serum, respectively. Evaluation of components of the NLRP3 inflammasome revealed an increased percentage of apoptosis‐associated speck‐like protein containing a CARD domain (ASC)‐expressing, caspase‐1‐expressing, and interleukin‐1β‐expressing cells in the myocardium and in the spleen of CVB3 + PBS vs. control mice, which was reduced in CVB3 + colchicine compared with CVB3 + PBS mice. This was accompanied by 1.4‐fold ( P < 0.0001), 1.7‐fold ( P < 0.0001), and 1.7‐fold ( P < 0.0001) lower numbers of cardiac dendritic cells, natural killer cells, and macrophages, respectively, in CVB3 + colchicine compared with CVB3 + PBS mice. A 1.9‐fold ( P < 0.05) and 4.6‐fold ( P < 0.001) reduced cardiac gene expression of the fibrotic markers, Col1a1 and lysyl oxidase, respectively, was detected in CVB3 + colchicine mice compared with CVB3 + PBS animals, and reflected by a 2.2‐fold ( P < 0.05) decreased Collagen I/III protein ratio. Colchicine further reduced Col3a1 mRNA and collagen protein expression in CVB3‐infected FB and lowered apoptosis and viral progeny release in CVB3‐infected HL‐1 cells. In both CVB3 FB and HL‐1 cells, colchicine down‐regulated the NLRP3 inflammasome‐related components ASC, caspase‐1, and IL‐1β. Conclusions: Colchicine improves LV function in CVB3‐induced myocarditis, involving a decrease in cardiac and splenic NLRP3 inflammasome activity, without exacerbation of CVB3 load.